2022
DOI: 10.3390/ijms23063102
|View full text |Cite
|
Sign up to set email alerts
|

Neuroelectric Mechanisms of Delayed Cerebral Ischemia after Aneurysmal Subarachnoid Hemorrhage

Abstract: Delayed cerebral ischemia (DCI) remains a challenging but very important condition, because DCI is preventable and treatable for improving functional outcomes after aneurysmal subarachnoid hemorrhage (SAH). The pathologies underlying DCI are multifactorial. Classical approaches to DCI focus exclusively on preventing and treating the reduction of blood flow supply. However, recently, glutamate-mediated neuroelectric disruptions, such as excitotoxicity, cortical spreading depolarization and seizures, and epilept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 145 publications
(241 reference statements)
0
50
0
3
Order By: Relevance
“…DCI occurs via a complex interplay among several concurrent processes including cerebral (angiographic) vasospasm, cerebral microcirculatory and neuroelectric disturbances including CSDs [6,9]. It was reported that the development of late-onset epileptiform discharges might cause DCI by triggering CSDs, or to a lesser extent directly [23].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…DCI occurs via a complex interplay among several concurrent processes including cerebral (angiographic) vasospasm, cerebral microcirculatory and neuroelectric disturbances including CSDs [6,9]. It was reported that the development of late-onset epileptiform discharges might cause DCI by triggering CSDs, or to a lesser extent directly [23].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the development of late-onset epileptiform discharges might cause DCI by triggering CSDs, or to a lesser extent directly [23]. CSD clusters are considered to induce inverted vasoconstrictive neurovascular coupling and then cerebral microcirculatory disturbances in compromised brain tissues after severe SAH, causing DCI [9,10]. Although seizure and CSD are biologically distinct phenomena, they are interlinked, and can trigger each other, worsening metabolic supply-demand mismatch and leading to progression of DCI after SAH [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations